One Health approach to investigate antimicrobial resistance and public health risk of foodborne pathogens in Gauteng and Limpopo provinces, South Africa - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2024)
Thesis (PhD (Medical Microbiology))--University of Pretoria, 2023.